2010
DOI: 10.1002/jhm.583
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation, management, and outcome of focal bacterial infections (FBIs) in nontoxic infants under two months of age

Abstract: BACKGROUND:Well‐appearing young infants with focal bacterial infections present to the emergency department (ED) and are often admitted for a sepsis evaluation of blood, urine, and spinal fluid. However, the risk of concomitant systemic infections (CSI) in this population is not well reported, specifically comparing febrile to afebrile infants. We hypothesized that afebrile, well‐appearing infants under two months of age with a defined focal bacterial infection on exam have a very low risk of CSI.METHODS:This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
(33 reference statements)
0
17
0
Order By: Relevance
“…Although the study included a total of 197 patients, in the subset of patients with SSTIs (n 5 136), 3 patients (2.2%, all of whom were febrile) had UTI or IBI (1 with Streptococcus pneumoniae bacteremia and 2 with Escherichia coli UTI). 8 Because the mechanism of UTI with SSTI is not apparent, it is worth noting that the authors of this article did describe a limitation of their study as being the definition of UTI based on culture (with no colony-forming unit specification) alone without supportive urinalysis findings. 8 Although our study used a similar culture-specific definition of UTI, we did maintain a threshold of $50 000 colony forming units/mL of a single organism.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Although the study included a total of 197 patients, in the subset of patients with SSTIs (n 5 136), 3 patients (2.2%, all of whom were febrile) had UTI or IBI (1 with Streptococcus pneumoniae bacteremia and 2 with Escherichia coli UTI). 8 Because the mechanism of UTI with SSTI is not apparent, it is worth noting that the authors of this article did describe a limitation of their study as being the definition of UTI based on culture (with no colony-forming unit specification) alone without supportive urinalysis findings. 8 Although our study used a similar culture-specific definition of UTI, we did maintain a threshold of $50 000 colony forming units/mL of a single organism.…”
Section: Discussionmentioning
confidence: 97%
“…8,10,11 One study of 104 afebrile infants #28 days who presented to the ED for SSTI found that none had IBI. 10 Another study of infants #30 days identified as having superficial or invasive S aureus infection found that of the 68 patients (total study cohort 126 patients) with cellulitis/abscess, 2 (3%) had bacteremia and none had concomitant UTI or meningitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The major limitations of the studies by Kharazmi et al and Vidwan and Geis are the low rate of performed LP (22 and 36%) and lack of follow-up data of enrolled infants which bear the potential for missed diagnosis of occult meningitis. No information regarding pleocytosis was provided in either of these studies 2 4. Walsh and McIntosh's work lacks stratification of data by fever status, and the number of infants that underwent an LP was relatively low (22%), which again raises concerns about missed diagnosis of occult meningitis 5…”
Section: Commentarymentioning
confidence: 99%